Efeitos da fragmentação florestal sobre a diversidade funcional e sobre grupos funcionais de aves - Schlichting, Mariana Sant’Ana [UNESP] (2013)
The Araucaria Forest suffered intense logging, and this fact led to the process of forest fragmentation. The imbalance caused by this process acts in different ways on species, functional groups and also on the functional diversity of birds. With the objective of evaluate the effects of forest fragmentation on species and functional groups and how this process affects the functional diversity of birds, we performed a compilation of works done in remnants of Araucaria Forest and tested (i) how species or functional groups influences the coupling between the remnants and, (ii) how processes such as the replacement of species is capable of maintaining functional traits communities. The results indicate that there are functional groups acting directly on the coupling between the remnants and that the process of species replacement is very important for the maintenance of functional traits within the community. This work also highlights the importance of species traits and functional groups to maintain the stability of the ecosystem